Quality of life and costs of spasticity treatment in German stroke patients - Reinhard Rychlik; Fabian Kreimendahl; Nicole Schnur; Judith Lambert-Baumann; Dirk Dressler (Health Economics Review, 2016)
Objective: To gather data about the medical and non-medical health service in patients suffering from post-stroke spasticity of the upper limb and evaluate treatment effectiveness and tolerability as well as costs over the treatment period of one year. Methods: Prospective, non-interventional, multicenter, parallel-group study comparing effectivenessand costs of incobotulinumtoxinA (INCO) treatment (n = 118) to conventional (CON) antispastic therapy (n = 110) for upper limb spasticity after stroke in 47 clinical practices across Germany over a 1-year treatment period. IncobotulinumtoxinA was applied according to the individual treatment algorithms of each participating site and additional antispastic treatments were allowed. Primary efficacy objective was the reduction of the muscle tone measured by Ashworth scale. Responder analyses and logistic regressions were performed. Quality of life, measured by SF-12 questionnaire and functional disability were assessed. Besides calculating treatment costs, a cost-utility analysis was performed. Results: Responder rates of all muscle groups of the upper extremities were significantly higher in the treatment group (62.9-86.2 % vs. 15.5-26.9 %, p < 0.01). Total health service costs were twice as high in the INCO group, however cost-utility ratios were consistently superior compared to the control group. Lowest incremental costs were documented to improve the 'physical health' dimension in quality of life. Conclusion: Higher responder rates, higher increases in quality of life and superior cost-utility ratios in the BoNT/A-treatment group underline guideline recommendations for botulinum toxin A treatment in focal or segmental spasticity. Results may partially be influenced by different patient demographics or disease severity at study entry.
Keywords: 330; Post-stroke spasticity; IncobotulinumtoxinA; Cost-utility; Ashworth score